2019
DOI: 10.1080/13218719.2019.1618750
|View full text |Cite
|
Sign up to set email alerts
|

Physical attractiveness and criminal justice processing: results from a longitudinal sample of youth and young adults

Abstract: A substantial body of research examining the role that attractiveness plays in a wide range of outcomes has revealed that attractiveness is a beneficial characteristic across multiple domains of life, including some related to crime and the criminal justice system. The current study uses these findings as a springboard to examine the potential association between attractiveness and multiple measures of criminal justice processing, including being arrested, being convicted, being sentenced to probation and bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…These results indicated that the advantageous effect of facial attractiveness was only found in those with low moral judgment. Previous research has found that high-facial-attractiveness defendants were considered less guilty at trial and received less severe punishment than low-facial-attractiveness defendants ( Efrain, 1974 ; Beaver et al, 2019 ; Bitton and Zvi, 2019 ; Petrauskaitė and Čunichina, 2019 ; Klein and Shtudiner, 2021 ). When low moral actors are subjected to painful stimuli, participants may be more forgiving and felt less aversive toward high facial attractive actors, and therefore showed stronger empathic responses.…”
Section: Discussionmentioning
confidence: 95%
“…These results indicated that the advantageous effect of facial attractiveness was only found in those with low moral judgment. Previous research has found that high-facial-attractiveness defendants were considered less guilty at trial and received less severe punishment than low-facial-attractiveness defendants ( Efrain, 1974 ; Beaver et al, 2019 ; Bitton and Zvi, 2019 ; Petrauskaitė and Čunichina, 2019 ; Klein and Shtudiner, 2021 ). When low moral actors are subjected to painful stimuli, participants may be more forgiving and felt less aversive toward high facial attractive actors, and therefore showed stronger empathic responses.…”
Section: Discussionmentioning
confidence: 95%
“…Within the field of criminal justice, attractiveness appears to also be related to offending [ 5 , 6 ]. If caught, being physically attractive may prove to be advantageous—with research indicating that physically attractive people are treated more leniently by criminal justice actors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…As it pertains to criminal justice, research suggests that physical attractiveness tends to afford individuals more lenience in the criminal justice system. Beaver et al [ 7 ] examined how physical attractiveness was related to involvement in criminal activity, arrest, conviction, incarceration, and probation. Using data from the National Longitudinal Study of Adolescent to Adult Health, the researchers found that people who were considered attractive were less likely to engage in criminal behavior and less likely to be arrested or convicted.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have found that attractive students get higher grades from their teachers (Begley, 2009). There are also speculations that attractive patients receive more personalized care from their doctors (Rumsey & Harcourt, 2005), are less likely to be arrested and convicted, and that handsome criminals receive lighter sentences than less attractive convicts (Beaver et al, 2019). On the contrary, unacceptable physical appearance may stigmatize and have a profound negative effect on psychological wellbeing.…”
Section: Introductionmentioning
confidence: 99%